2018
DOI: 10.1111/nmo.13286
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the gut barrier and involvement of Toll‐like receptor 4 in murine postoperative ileus

Abstract: These results indicate that GB is impaired in the experimental POI, with inflammation being involved in this pathological process. TLR4 deficiency alleviated GB dysfunction and suppressed inflammation by disrupting the activation of mitogen-activated protein kinase signaling pathways, thereby ameliorating POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…Consistent with earlier ndings, we observed a signi cant increase in the levels of pro-in ammatory cytokines in the blood of POI animals 10,29 . These in ammatory mediators contribute to the decreased GI motility associated with POI through various mechanisms such as direct cytotoxic effects and induction of nitricoxide (NO) and prostanoid production 30 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with earlier ndings, we observed a signi cant increase in the levels of pro-in ammatory cytokines in the blood of POI animals 10,29 . These in ammatory mediators contribute to the decreased GI motility associated with POI through various mechanisms such as direct cytotoxic effects and induction of nitricoxide (NO) and prostanoid production 30 .…”
Section: Discussionsupporting
confidence: 92%
“…POI increases the risk of postoperative complications and morbidity 3 . Recent studies have shown that postoperative in ammatory reactions are involved in the development of POI 10,13,14 . Consistently with earlier reports 6,7 , at 24 and 48 h after intestinal manipulation, we observed a signi cant decrease in GI transit rate, induction of an in ammatory response characterized by leukocyte in ltration in the intestinal tissue, villous epithelial cell structural damage, submucosal edema, hyperemia, and epithelial cell necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations